Efficiency of water spraying on a heat exchanger: Local characterization with the impacted surface. (5th January 2018) - Vende, P.E.; Trinquet, F.; Lacour, S.; Delahaye, A.; Fournaison, L.
Highlights: Heat transfer enhancement of water spraying is higher at low surface temperature. A thermal image analysis is used to assess the efficient cooling surface. The efficient cooling surface is relevant to water spraying efficiency evaluation. The impacted surface depends on the surface temperature, not on the air flow. Spraying efficiency strongly depends on the local water-to-air mass flux ratio. Abstract: Due to climate change, worldwide power consumption for air conditioning is forecasted to increase by 33 times its current level by 2100. To face this trend, the efficiency of air conditioning and refrigeration systems must increase. Water spraying on the condenser of a refrigeration unit is one solution to reach this aim. Indeed, spraying water on a heat exchanger improves heat transfer by adiabatic cooling or direct impact on the heat-exchanger surface. In the present paper, water spraying is designed for an embedded air conditioning application. A pilot designed for air conditioning conditions was built and equipped with a set of atomizer. The results obtained with this pilot show that heat transfer enhancement is higher at low heat exchanger surface temperature. Moreover, a thermal image analysis has highlighted that the surface impacted by the spray excluding the clogged parts is appropriate to express the local efficiency of the spray. Indeed, this surface reaches a steady-state approximately after the same time than heat transfer enhancement. This surface depends on heat-exchanger surface temperature, and not on the air flow. Finally, the efficiency of water spraying on a heat exchanger is correlated with the impacted surface.